Genetic variation in the banana cultivar Sukali ndizi grown in different regions of Uganda - Pillay, M.; Dimkpa, C.O.; Ude, G.; Makumbi, Dan; Tushemereirwe, Wilberforce K. (2003)
Banana is an important food and cash crop in Uganda. The crop displays wide diversity but the genetic relationship between and withing cultivars is largely unknown. A study was conducted to assess genetic relationships among 'Sukali Ndizi' clones collected from 16 different localities in Uganda using the random amplified polymorphic DNA (RAPD) and amplified fragment length polymorphism (AFLP) techniques. Thirty-four RAPD primers used singly and in combination produced 234 unambiguous bands. The RAPD primers produced identical banding patterns in all the samples and were, therefore, not useful in differentiating the clones. However, the 9 AFLP primer pairs produced 554 fragments, 17 of which were polymorphic. Genetic relationships were established from the AFLP data by cluster analysis. Two groups of clones were clearly defined. Clones from selected contiguous districts such as Lira and Soroti, Bushenyi and Kasese districts were highly similar. Other closely related clones were from disjunctive localities. The similarity of the clones in adjacent districts is attributed to local exchange of germplasm, while similarity of clones in non-contiguous districts is probably the result of more purposeful and selective transfer of planting material. In general, the observed clonal variation may be due to somatic mutations.